RESIDENTS' SATISFACTION WITH DWELLINGS AS CORRELATE OD PERSONALIZATION IN SELECTED PUBLIC HOUSING ESTATES IN LAGOS, NIGERIA - Morakinyo, Kolawole Opeyemi; Ilesanmi, Adetokunbo O. (ARTEKS : Jurnal Teknik Arsitektur, 2020)
In the field of architecture, personalization refers to the process through which an individual modifies or alters an element, space or form, to make it distinctly his or her own. Nevertheless, this concept has been of interest in diverse contexts, especially within the context of public housing. This study examine residents? satisfaction with dwellings as correlate of personalization in selected public housing estates in Lagos, Nigeria. Specifically, the study assess resident?s satisfaction with dwellings; ascertain the level of personalization of dwellings; and examined the relationship between satisfaction with dwellings and personalization.  The study utilized a survey research design, in which primary data were collected using structured questionnaire and personal observations. Four public housing estates were purposively selected comprising three low-income and one medium-income housing estate out of 22 low-income and 10 medium-income estates, being the largest estates. The sampling frame comprised 9734 housing units from which a sample size of 973 housing units were selected using systematic random sampling technique. Findings revealed majority of the respondents were not satisfied with the general design and style of the building when they first moved in (98.1%). Respondents not satisfied with the design of the building because it did not give consideration to gender differences constituted (97.4%). Almost all (99.3%) of the respondents reported the original design of their building not meeting their different housing needs, while significant proportion (96.1%) had complained about certain aspects of their house not meeting some specific needs of their family. The level of personalization of dwellings in the study area was quite high. Overall, regardless of the selected housing estate, about two thirds (62.0%) of the residents had personalized their dwelling units. The level of satisfaction was significantly associated with personalization. Higher likelihood of personalization of dwellings was found among respondents who were not satisfied with the design and style of their building when they first moved in (OR=7.09, p<0.05), those who stressed that the design of their house did not give consideration to gender differences (OR=7.17, p<0.05) and residents who lived permanently in their apartment (OR=1.68, p<0.05). Lower likelihood of personalization of dwelling was however found among residents who had another house apart from the one they were currently residing (OR=0.65, p<0.05).  This study, therefore, underscores the importance of satisfaction with dwellings as a correlate of personalization of dwellings in public housing estates.